Meningkatkan Pelayanan Pelanggan dengan Sistem Informasi Manajemen: Membangun Loyalitas dan Keunggulan Kompetitif - Balqis Humaira; Rayyan Firdaus (Jurnal Manajemen Kewirausahaan dan Teknologi, 2024)
Management Information System (MIS) is an important tool for companies to manage information and support business processes. However, there are still many companies that have not utilized SIM optimally to improve customer service. This research uses a qualitative case study method to collect data. This research examines the role of Management Information Systems (MIS) in improving customer service quality, building customer loyalty, and achieving competitive advantage in the digital era. The findings show that SIM plays an important role in improving the five dimensions of customer service quality, namely reliability, responsiveness, assurance, empathy, and form. SIM is also proven to help build customer loyalty through increased satisfaction, trust, and commitment. In addition, SIM can help companies achieve a competitive advantage by increasing customer retention, attracting new customers, and improving the company's image.